AN INVESTIGATION INTO APOLOGY STRATEGIES AND LEXICOGRAMMATICAL REALIZATIONS OF APOLOGY UTTERANCES IN ENGLISH CONVERSATIONS - Ngo Thi Hien Trang (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
This research aims to investigate the types of apology strategies and lexicogrammatical realizations of apology utterances in English conversations extracted from films with romance and family contexts. A theoretical framework of the study was provided to set a light for the researcher to follow. In order to find the answer to four research questions, this study made use of the coding system of the apology strategy taxonomy by Trosborg (2011), and the lexicogrammar approach by Halliday and Matthiessen (2013). This is descriptive qualitative research with the support of the quantitative. The findings of this research depict the whole picture of apology strategies used by bottom by the characters in English-language conversations from film scripts and subtitles. To make it specific, direct strategies were the most frequently used, whereas, the newly-discovered apology strategy of mixed apology strategy stood at the bottom. Regarding lexicogrammatical realizations of apology utterances, the pattern of [Apologizer + Verb + Apologizing] reached its peak which included 2 lexicogrammatical realizations namely [I’m sorry] and [I beg your pardon].